Sensing Health Bodies, Data, and Digital Health Technologies - Kressbach, Mikki (Digital Culture Books, 2024)
In the age of Apple Watches and Fitbits, the concept of "health" emerges through an embodied experience of a digital health device or platform, not simply through the biomedical data it provides. Sensing Health: Bodies, Data, and Digital Health Technologies analyzes popular digital health technologies as aesthetic experiences to understand how these devices and platforms have impacted the way individuals perceive their bodies, behaviors, health, and well-being. By tracing design alongside embodied experiences of digital health, Kressbach shows how these technologies aim to quantify, track and regulate the body, while at the same time producing moments that bring the body's affordances and relationship to the fore. This mediated experience of "health" may offer an alternative to biomedical definitions that define health against illness. To capture and analyze digital health experiences, Kressbach develops a method that combines descriptive practices from Film and Media Studies and Phenomenology. After examining the design and feedback structures of digital health platforms and devices, the author uses her own first-person accounts to analyze the impact of the technology on her body, behaviors, and perception of health. Across five chapters focused on different categories of digital health-menstrual trackers, sexual wellness technologies, fitness trackers, meditation and breathing technologies, and posture and running wearables-Sensing Health demonstrates a method of analysis that acknowledges and critiques the biomedical structures of digital health technology while remaining attentive to the lived experiences of users. Through a focus on the intersection of technological design and experience, this method can be used by researchers, scholars, designers, and developers alike.